TIME-DRIVEN opportunistic routing protocol for ultra-wideband indoor positioning. (December 2016) - Gao, Qian; Shen, Chong; Dong, Fang; Chen, Xiaosi; Xie, Xingang; Wang, Wensi; Zheng, Liqiang
The scope of a single regional indoor positioning network is often restricted to its main anchor communication range and more susceptible to obstacles. Multiple main anchors can be the basis of an indoor positioning network's extensibility and can adapt to the complex communication environment. In this article, a novel TIME-DRIVEN opportunistic routing protocol with intelligent response is proposed. First, an extendable ultra-wideband positioning system is modeled. In two or more communication cells, anchors can act as a main or slave anchor in different areas, respectively, and a forward clock check package from the initial district to its surrounding area. They can also achieve the clock synchronization of the entire network. In this model, the anchors will be divided into different sizes of clusters, and the main anchor is elected according to the broadcast time. Furthermore, the relay anchor will be intelligently selected according to the opportunistic probability based on the received signal strength indicator. Finally, experiments are conducted to verify the performance of the method.